In silico modeling and empirical study of 4-n-Butylresorcinol nanoliposome formulation. Issue 21 (5th December 2022) - Dwiastuti, Rini; Radifar, Muhammad; Putri, Dina Christin Ayuning; Riswanto, Florentinus Dika Octa; Hariono, Maywan
Abstract: A study to incorporate in silico modeling with an empirical experiment has been carried out to formulate nanoliposome containing 4- n -butylresorcinol as the active ingredient. The in silico modeling was performed using molecular dynamics simulation followed by radius of gyration observation to provide insight into the mechanisms of 4- n -butylresorcinol stabilization by liposome due to their nano-size. The empirical experiment was conducted by formulating the nanoliposome using soy lecithin phospholipid formula as suggested by the in silico modeling followed by determining its particle size as well as its shape. From their incorporation, it was found that 3200 phospholipid molecules were selected in formulating nanoliposome containing 4- n -butylresorcinol. The results of the nanoliposomes size observation in the modeling of 3200 lipid molecules was 87.01 (± 0.59) nm, whereas the size from the empirical study was 87.57 (± 0.06) nm. Communicated by Ramaswamy H. Sarma